The Privatization of Israel The Withdrawal of State Responsibility (Palgrave Macmillan US, 2018)
The book is the first to cover all areas of privatization in Israel and one of the first to do so in general, including state infrastructure, immigration policy, land, health, education, welfare, regulation, and policy design. As such, it offers a comprehensive volume for students, policy makers, and scholars interested in the economic, sociological, political, and legal perspectives of a major policy trend that has changed the face and character of the modern state. In addition, it is a vital contribution to those who have an interest in changes in Israeli society, politics, and economy.